New OECD Methods for Supply-side and Medium-term Assessments A Capital Services Approach - Beffy, Pierre-Olivier (OECD Economics Department Working Papers, 2006)
The OECD makes frequent use of the supply-side framework and associated measures of factor productivity, productive potential and associated output gaps in the assessment of the short-term conjunctural situation, comparative economic performance and longer-term growth determinants. This paper describes a number of recent changes and improvements in the methods used in estimating potential output for OECD countries and the systems in which they are used, notably for the production of mediumterm economic scenarios. By and large, these reflect important changes and improvements in available statistical data sets, notably for measuring productive capital, as well as the development of more efficient model-based methods for making medium-term projections on a consistent international basis